Business People in War Times, the ‘shy Capital’ and Diaspora Business: the Case of Syrian Refugees in Turkey - Görmüş, Evrim; Akçalı, Emel (My University, 2019)
This presentation focuses on the Syrian capital flight to Turkey to examine the capacity and/or willingness of the Syrian diaspora business community to organize themselves as interest groups regarding their political and economic interests in Turkey, and to assist the process of conflict resolution and post-conflict reconstruction in Syria with a focus on remittances, philanthropy work and participation in peace processes etc.The presentation is based on fieldwork carried out inIstanbul, Adana, Mersin, Hatay, Gaziantep and Bursa, where the majority of the Syrian business is located. We conducted a total of 35 individual semi-structured in-depth interviews with Syrian businesspeople, civil society representatives and local chamber of commerce officials in August-October 2018. Based on the findings of our fieldwork, we argue that the patterns of the Syrian business diaspora engagement in Turkey are mainly shaped by the spatial elements, such as the increasing transnationalization of economic practices in the course of the protracted conflict as well as the historical legacies of state, business and market structure in the pre-war Syria.
Keywords: Transnationalization; Post-conflict; Syrian conflict; Business diaspora; Capital flight